2015
DOI: 10.30861/9781407314242
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Development of Ancestral Polynesian Society in Tonga

Abstract: Patrick V. Kirch and Roger C. Green proposed that Polynesian cultures today emerged and developed in an ancestral homeland situated in western Polynesia, primarily Tonga and Sāmoa. The archaeological marker for the beginnings of cultural and linguistic divergence from a founding Eastern Lapita base is Polynesian Plainware pottery produced for nearly 1,100 years during the Polynesian Plainware phase. Kirch and Green believe this transition reflects social and economic changes that led to the development of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The addition of three high precision U/Th dates are of some importance in this respect though, especially in consideration of recent re‐dating and Bayesian analysis of the To'aga site, 650 km to the northeast on Ofu Island, American Sāmoa (Petchey & Kirch 2019). To'aga does not have decorated Lapita wares, nor does the undecorated ceramic assemblage (Hunt & Erkelens 1993) relate to the Polynesian Plainware phase as defined for Tonga (Connaughton 2015). Yet its modelled chronology with the first settlement in the range of 2785–2607 calBP (68.2%) seemingly overlaps with colonisation events in Vava'u and Ha'apai.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of three high precision U/Th dates are of some importance in this respect though, especially in consideration of recent re‐dating and Bayesian analysis of the To'aga site, 650 km to the northeast on Ofu Island, American Sāmoa (Petchey & Kirch 2019). To'aga does not have decorated Lapita wares, nor does the undecorated ceramic assemblage (Hunt & Erkelens 1993) relate to the Polynesian Plainware phase as defined for Tonga (Connaughton 2015). Yet its modelled chronology with the first settlement in the range of 2785–2607 calBP (68.2%) seemingly overlaps with colonisation events in Vava'u and Ha'apai.…”
Section: Discussionmentioning
confidence: 99%
“…95). Source: Derived from Burley et al (2002); Connaughton (2014); Kirch (1988) and Poulsen (1987). Late Lapita decoration in Tonga is characterised by expanded and simplified dentate-stamped designs that are consistently applied across the range of vessel forms (Burley et al 2002:220, 223;Connaughton 2014:166).…”
Section: Regional Profiles Tongamentioning
confidence: 99%
“…2). This broad grouping is acknowledged(Burley et al 2002:217, 223) but it has also demonstrated that carinated sherds are a dominant feature of many sites and often associated with decoration(Burley et al 2002:Table 4;Connaughton 2014; Kirch 1988:158).…”
mentioning
confidence: 99%
“…2009), Tonga (Poulsen 1987: 163; Clark et al . 2014; Connaughton 2014) and Samoa (Best et al . 1992; Green et al .…”
Section: Site Overview Materials and Prior Researchmentioning
confidence: 99%
“…The current data paint a picture of interaction, but also innovation in isolation (Davidson 2012). It appears that the cultural sequence of West Polynesian adze designs is driven by substantial amounts of conservatism where early innovations persisted (Connaughton 2014; Smith 2002). Differences in adze morphologies, for example, the lack of triangular forms in Tonga and oval/round adzes Samoa, continued through a period of lower inter‐island interaction in the Plainware Period of both island groups.…”
Section: Site Overview Materials and Prior Researchmentioning
confidence: 99%